Molecular profiling of clinical remission in psoriatic arthritis reveals dysregulation of FOS and CCDC50 genes: a gene expression study - Angioni, Maria Maddalena; Floris, Alberto; Cangemi, Ignazio; Congia, Mattia; Chessa, Elisabetta; Naitza, Micaela Rita; Piga, Matteo; Cauli, Alberto (Frontiers in Immunology, 2023)
Background In psoriatic arthritis (PsA) the primary goal of treatment is clinical remission. This study aimed to characterize the molecular profile underlying the induced clinical remission in patients with PsA, comparing the remission state versus the healthy condition.The whole blood transcriptomic analysis was performed on groups of: 14 PsA patients in TNFi-induced clinical remission (DAPSA ≤4); 14 PsA patients with active disease (DAPSA >14); and 14 healthy controls (HCs). Then, all dysregulated expressed genes (DEGs) derived from remission vs HCs comparison were analyzed for functional and biological characteristics by bioinformatics software. Gene expression of twelve genes were then validated by RT-qPCR in an extended cohort of 39 patients in clinical remission, 40 with active disease and 40 HCs.The transcriptomic analysis of PsA remission vs HCs highlighted the presence of 125 DEGs, out of them, 24 were coding genes and showed a great involvement in immune system processes and a functional network with significant interactions. The Rt-qPCR validation confirmed the down-and up-regulation of, respectively, FOS (FC -2.0; p 0.005) and CCDC50 (FC +1.5; p 0.005) genes, in line with their role in orchestrating inflammation and bone metabolism processes, may be related to PsA pathophysiology.The transcriptomic profile of clinical remission in PsA is similar to healthy condition, but not identical, differing for the expression of FOS and CCDC50 genes, which appears to play a key role in its achievement.